Percepción del rendimiento y motivación académica a causa de la educación virtual a los estudiantes del programa de odontología de la universidad Antonio Nariño sede Palmira, en el marco de la pandemia por COVID 19 (2022)
This project was a quantitative, observational, descriptive, crosssectional study whose purpose was to analyze the academic performance and motivation due to virtual education of the students of the dentistry program of the Antonio Nariño University, Palm ira headquarters, in the framework of the pandemic. by COVID 19.